Immunohistochemical and karyometric similarities and differences of salivary gland tumors between pleomorphic adenoma, basal cell adenoma and polymorphous low grade adenocarcinoma - Živković Nikola D.; Mihailović Dragan S.; Kostić Miloš S.; Cvetanović Ana S.; Denčić Tijana V.; Jovičić-Milentijević Maja V.; Mijović Žaklina Ž; Stojanović Simona M.; Spasić Milan S.; Pešić Zoran U.; Trajković Miloš N. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2017)
Introduction: Salivary gland tumors are extremely rare neoplasms. Given their pathohistological image, these tumors represent a great diagnostic challenge. The aim of our study was to differentiate these three tumor types by applying the immunohistochemical and morphometric analysis. Material and Methods: The entire study was conducted at the Center for Pathology and Pathological Anatomy in Niš. The study included 44 tumors, 20 pleomorphic adenomas, 12 basal cells adenomas and 12 polymorphous low-grade adenocarcinomas. The expression of Ki67, p53 and HER-2 antigens, as proliferation markers, was analyzed. The differential diagnostics also included the analysis of the expression of CEA, EMA, GFAP, p63, vimentin, CK14, α-SMA, S-100 protein and WT1 antigen. The morphometric analysis was done in the program pack 'ImageJ' version 1.43u. The statistical analysis of data was done in the program pack SPSS 15.0. Results: Neoplastic cells in pleomorphic adenoma showed a strong expression of GFAP (20/20), p63 (20/20), WT1 (20/20), vimentin (18/20) and S100 (16/20). Diffuse expression of CK14 (12/12) was present in the group of 12 polymorphous low-grade adenocarcinomas. S-100, vimentin and EMA were absolutely expressed, whereas α-SMA was negative. Basal cell adenoma showed negativity to S-100, CEA, p63 and vimentin. The analysis of the proliferative Ki67 index values pointed to a statistically significant difference in the pleomorphic adenoma group, which was associated with a frequent recurrence of this benign tumor. The analysis of morphometric characteristics showed higher values in the polymorphous low-grade adenocarcinoma group, but statistically significant differences were found only for the Feret diameter and the integrated optical density (p < 0.05). As for the basal cell adenoma group, tumor cells showed statistically higher values for the integrated optical density (p < 0.001). Conclusion: Apart from the basic micromorphological analysis, the differential analysis of salivary gland tumors also requires the immunohistochemical analysis as well as the monitoring of morphometric characteristics of these tumors' nuclei.